NARRATIVE REVIEW: THE ROLE OF GENETIC ENGINEERING AND DNA REPLICATION IN THE FORMATION OF SUPERIOR SHALLOT VARIETIES - Mohamad Rafiq Putera Amir; Fidiyah Rahadatul 'Aisy Husain; Nasywa Sabili Usulu Bilondatu; Deswita Faradila Sango; Nurindah Yuliyani Usman; Nurul Ilmi Mardatilah (JIMR : Journal Of International Multidisciplinary Research, 2025)
Shallots are an important horticultural commodity in Indonesia, but their productivity remains low due to limited superior varieties, high susceptibility to disease, and decreased vigor resulting from the continuous use of bulbs as seeds.. This study aims to assess the effectiveness of polyploidy induction and the role of DNA replication in the formation of superior onion varieties through a literature review of three major journals. The method used was a literature study by searching for articles related to genetic engineering, in vitro culture, the use of colchicine, and changes in plant phenotypes through the PubMed, ScienceDirect, and Google Scholar databases. The results showed that colchicine can inhibit spindle fiber formation during cell division, thereby promoting DNA replication without chromosome separation and producing polyploid plants with larger cells and organs. The application of colchicine in in vitro culture, meristem, and True Shallot Seed (TSS) has been proven to increase bulb size, improve morphological characteristics, and increase plant vigor. In addition, TSS offers advantages such as longer storage life, pathogen-free, and more uniform growth.